2019
DOI: 10.1039/c9na00246d
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of a polymer-based hole transporting layer for application in planar inverted perovskite solar cells

Abstract: Operational stability and structural integrity of a poly(triarylamine) hole transporter and methylammonium lead halide absorber are investigated upon exposure to UV stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 78 publications
2
31
0
Order By: Relevance
“…Moreover, the properties of the HTL not only impact the crystal growth and optoelectronic properties of the perovskite layer but also influence the device operational stability. The HaPSCs with PTAA and NiO x have different degradation rates because the PTAA and NiO x have different interface chemistries and interactions with external stimuli. , In this work, we focus to get insights into the degradation phenomena of these devices under thermal and light stress.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Moreover, the properties of the HTL not only impact the crystal growth and optoelectronic properties of the perovskite layer but also influence the device operational stability. The HaPSCs with PTAA and NiO x have different degradation rates because the PTAA and NiO x have different interface chemistries and interactions with external stimuli. , In this work, we focus to get insights into the degradation phenomena of these devices under thermal and light stress.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Therefore, we have strong indication that the ETL configuration not only affects the charge extraction characteristics at the interface, but also improves the mobility within the perovskite film for PSCs with c(Li)-NP-SnO 2 as ETL as compared to c-SnO 2 and c(Li)-SnO 2 . [102][103][104][105]…”
Section: Materials Advances Papermentioning
confidence: 99%
“…In addition, injection of hole from perovskite to HTL is allocated to the second decay component (τ 2 ). [ 40,41,43 ] Similar to τ 1 , fitted data showed that the faster τ 2 decay components can also be observed when PTAA is used as HTL in perovskite devices under different pump fluencies, as shown in Table 3. However, the τ 2 decay components for other HTLs showed exactly a similar trend as that of τ 1 , but P9VK‐based devices exhibited a quicker τ 2 decay component as compared to the NiO‐NC and PEDOT:PSS at higher fluence (15 µJ cm −2 ), which might be attributed to large grain size of perovskite film on P9VK HTL.…”
Section: Resultsmentioning
confidence: 85%
“…τ 1 actually is the time of an excited electron during which it shifts from conduction band of perovskite to trap states. Therefore, the smaller the time component τ 1 , the faster trap filling, which leads to larger splitting in the quasi‐Fermi energy levels [ 41 ] and consequently an enhancement in all the device parameters. Moreover, it should be noted that the density of trap states and their depth exerts a noticeable effect on τ 1 constant.…”
Section: Resultsmentioning
confidence: 99%